Research on Integrated Energy Technology of Green Campus Combined with Wind, Solar, Storage, Charging, Industry, Academia and Research. Issue 1 (August 2020) - Long, Min; Hu, Bizheng; Wei, Meifang; Han, Chaowei; Cheng, Xiang; Yang, Jing
Abstract: The research on the integration of wind, solar, storage, charging, industry, academia and research is an important embodiment of promoting the traditional energy system to step forward into the energy Internet system. The green smart campus is also a typical demonstration of the energy Internet. In this paper, an integrated construction scheme of wind, solar, storage, charging, industry, academia and research is put forward in combination with the actual situation. In order to realize multi-energy complementarity in a more scientific way, the operation mode of the micro-grid system is studied and analyzed in depth under grid-connected and off-grid modes, so that the emergency power for critical loads can be guaranteed when power is lost. The scheme provides a set of new and concrete solutions for colleges and universities to realize green and smart campus.